2006
DOI: 10.1007/s10457-005-2916-0
|View full text |Cite
|
Sign up to set email alerts
|

Tree Regeneration and Sapling Damage of Pedunculate Oak Quercus robur in a Grazed Forest in Galicia, NW Spain: A Comparison of Continuous and Rotational Grazing Systems

Abstract: Forest grazing has been recognised as being a useful tool in fire-risk reduction, in addition to having the potential to preserve or enhance forest biodiversity if managed correctly. Concern for natural regeneration of forest trees in Europe has also prompted interest in the effects of large herbivores on seedling and sapling growth and mortality. An investigation was carried out into sapling damage and density of natural regeneration of oak (Quercus robur) in a mature, pony-grazed, Pinus radiata forest in Gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
1
14
1
Order By: Relevance
“…This finding indicates that livestock grazing may be one of the factors facilitating plant species regeneration in least and moderately grazed areas mainly due to the role it plays in reducing competition through grazing and browsing which promotes plant species diversity. This is consistent with the observation made by [15] that low level of livestock grazing increases natural regeneration through reducing competition among plant species in a community. This study observed low diversity of regenerants in ungrazed areas ( Table 3).…”
Section: Discussionsupporting
confidence: 93%
“…This finding indicates that livestock grazing may be one of the factors facilitating plant species regeneration in least and moderately grazed areas mainly due to the role it plays in reducing competition through grazing and browsing which promotes plant species diversity. This is consistent with the observation made by [15] that low level of livestock grazing increases natural regeneration through reducing competition among plant species in a community. This study observed low diversity of regenerants in ungrazed areas ( Table 3).…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that a light level of grazing can increase tree regeneration by removing competitive vegetation, reduce fire hazard and fertilization from manure (Kuiters et al, 1996;McEvoy et al, 2006). Large herbivores can also create patches of bare ground through grazing and trampling.…”
Section: Introductionmentioning
confidence: 99%
“…Lempesi et al (2013) results in a grazed oak woodland in northern Greece confirmed the moderate grazing hypothesis (Noy Meyer, 1995;Tilman, 1997) that light and moderate grazing results in an increase of biodiversity. Thus, managed woodland grazing systems are increasingly recognised as being beneficial to woodland biodiversity (McEvoy et al, 2005).…”
Section: Resultsmentioning
confidence: 99%